2015
DOI: 10.1007/s00520-015-2738-1
|View full text |Cite
|
Sign up to set email alerts
|

Study of rolapitant, a novel, long-acting, NK-1 receptor antagonist, for the prevention of chemotherapy-induced nausea and vomiting (CINV) due to highly emetogenic chemotherapy (HEC)

Abstract: All doses of rolapitant were well tolerated and showed greater CR rates than active control. Rolapitant 180 mg demonstrated significant clinical efficacy for preventing CINV in the overall, delayed, and acute phases for patients receiving HEC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 31 publications
4
78
0
Order By: Relevance
“…The phase II cisplatin-based HEC (NCT00394966) [16], phase III cisplatin-based HEC-1 (NCT01499849) and cisplatin-based HEC-2 (NCT01500213) [17], and phase III moderately emetogenic chemotherapy or AC-based chemotherapy (NCT01500226) [18] randomized, double-blind, parallel-group trials enrolled patients scheduled to receive their first chemotherapy treatment. Eligibility criteria for these studies have been described [16–18] and are included in the supplementary material, available at Annals of Oncology online.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The phase II cisplatin-based HEC (NCT00394966) [16], phase III cisplatin-based HEC-1 (NCT01499849) and cisplatin-based HEC-2 (NCT01500213) [17], and phase III moderately emetogenic chemotherapy or AC-based chemotherapy (NCT01500226) [18] randomized, double-blind, parallel-group trials enrolled patients scheduled to receive their first chemotherapy treatment. Eligibility criteria for these studies have been described [16–18] and are included in the supplementary material, available at Annals of Oncology online.…”
Section: Methodsmentioning
confidence: 99%
“…In randomized phase II and III trials, a single 180-mg oral dose of rolapitant with a 5-HT 3 RA and dexamethasone regimen on the same day as chemotherapy provided superior protection against nausea and/or vomiting on days 2–5 after chemotherapy [16–18]. The safety profile of rolapitant was consistent across studies, with a low incidence of treatment-related AEs generally comparable to that observed in control arms [16–18]. Unlike other approved oral NK 1 RAs [19], rolapitant does not induce or inhibit CYP3A4 [20, 21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It exhibits the longest half life (180 hours) in this drug class and occupies CNS NK 1 receptors for >5 days (34). In a phase 2 trial, rolapitant produced significantly better complete responses in CINV versus a regimen of ondansetron plus dexamethasone (35). In three phase 3 investigations, this agent elicited higher responses particularly in the delayed phase of CINV than control groups who received a 5-HT 3 antagonist and corticosteroid (36).…”
Section: Medications Used To Treat Nausea and Vomitingmentioning
confidence: 99%
“…Patients in the rolapitant group had a significantly higher CR rate in the acute, delayed and overall phases compared to granisetron and dexamethasone plus placebo. Moreover, the rolapitant group achieved higher rates of complete protection in both delayed and overall phases (32,33).…”
Section: Neurokinin 1 Receptor Antagonists: the New Drugsmentioning
confidence: 99%